1997
DOI: 10.1046/j.1365-2982.1997.d01-40.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lower oesophageal sphincter pressure measurement using circumferential vs unidirectional transducers

Abstract: UND and CMF transducers provide identical measurements when evaluating the LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, the volunteers underwent the two manometries in random order and the bias may be reduced as much as possible. Pursnani et al has demonstrated a high degree of correlation between measurements made with circumferential transducers compared to the sum of four unidirectional transducers in measuring resting LES pressures [6]. Our further analysis also presented the consistency of the measurements from the two systems by Bland–Altman plots.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the volunteers underwent the two manometries in random order and the bias may be reduced as much as possible. Pursnani et al has demonstrated a high degree of correlation between measurements made with circumferential transducers compared to the sum of four unidirectional transducers in measuring resting LES pressures [6]. Our further analysis also presented the consistency of the measurements from the two systems by Bland–Altman plots.…”
Section: Discussionmentioning
confidence: 55%
“…Besides, the patterns of luminal pressure perception and conversion of the pressure signal into an electrical signal are different, pressure measurements from the two manometers may exist differences. Castell et al [5] and Pursnani et al [6] performed trials comparing SSC and WPC focused on pharyngeal, upper oesophageal sphincter and lower oesophageal sphincter pressure measurement. However, in the times of their trials, the manometry catheter was only equipped with small number of transducers.…”
Section: Introductionmentioning
confidence: 99%
“…They had the advantage of an extremely high response rate, making them useful for detecting the rapid pressure changes in the UES, but the disadvantage of fragility, high cost, and the inconvenience of repair if one of the transducers on a catheter malfunctioned. 49 The technology of Micro-Electrical-Mechanical-Systems (MEMS) progressed rapidly, allowing transducers to be extremely small. 50 For motility studies, it was eventually possible to create a flexible catheter only 4.2 mm in diameter, with 12 tiny transducers round the circumference at 1 cm intervals.…”
Section: The Emergence Of High Resolution Manometrymentioning
confidence: 99%